Science Experiments You Can Eat - Vicki Cobb (Harper, an imprint of HarperCollins Publishers, 2016)
With revised and updated material, a brand-new look, and hours of innovative, educational experiments, this science classic by award-winning author Vicki Cobb will be devoured by a whole new generation of readers! Kids take the reins in the kitchen with this hands-on book of edible science experiments. With contemporary information that reflects changes in the world of processing and preserving foods, this cookbook demonstrates the scientific principles that underpin the chemical reactions we witness every day-just by cooking. And once readers have tested their theories and completed their experiments, they can eat the results! From salad dressing to mayonnaise, celery to popcorn, and muffins to meringues, this book uses food to make science accessible to a range of tastes. Also included is essential information on eating healthfully, plus additional resources for further exploration.